A new species of Allagoptera (Arecaceae) from the Cerrado of central Brazil - Martins, Renata Corrêa; Filgueiras, Tarciso S.; Graciano-Ribeiro, Dalva; Somavilla, Nádia Sílvia (Phytotaxa, 2015)
A new species of Allagoptera from the Cerrado of central Brazil is described. The new species is distinguished by its solitary habit, open crown, and very long inflorescence rachis conspicuously curved at maturity. The new species, A. robusta, is compared morphologically and anatomically with A. campestris and A. leucocalyx.